Estimation of the mechanical properties of urea–formaldehyde microcapsules by compression tests and finite element analysis. Issue 19 (29th January 2016) - Ma, Wanpeng; Zhang, Wei; Zhao, Yang; Wang, Sijie
ABSTRACT: Information on the mechanical properties of microcapsules is essential to understanding their performance during manufacturing, processing, and applications. The mechanical properties of urea–formaldehyde (UF) microcapsules filled with ethyl phenyl acetate (EPA) were determined by applying single‐microcapsule compression and a finite element model. Microcapsules were prepared by in situ polymerization, and the average wall thickness of microcapsules was 192 ± 12 nm as determined using scanning electron microscopy. The deformation behavior of the microcapsule was measured by a single‐microcapsule compression experiment between two parallel plates. The results show that both burst deformation and burst force were linearly related to microcapsule size. A model for an elastic shell filled with incompressible fluid was used to simulate compression of the microcapsule in ABAQUS. Dimensionless parameters were introduced to the model. The relationship between dimensionless force and dimensionless displacement depended on the ratio of wall thickness to diameter (ε). However, the relationship remained the same when ε was less than 1% and can be fitted well by the mathematical equation. An estimation of Young's modulus can be obtained from the compression data for the dimensionless deformation from 10% to 15%. The average Young's modulus of a UF/EPA microcapsule is estimated to be 2.12 ± 0.45 GPa. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43414. Abstract :